Innovative Approach to the Optimal Distribution of Citizens’ Pension Savings to Non-State Pension Funds - Kostyrin, Evgeniy; Drynkin, Stepan (Ital Publication, 2025)
In the Russian Federation, persistent economic and legal tensions surround the allocation of citizens’ pension savings; however, individuals retain the option to select the organization that manages the funded portion of their pension. This study aims to address the challenges posed by dynamic programming regarding the optimal distribution of Russian citizens’ pension savings to non-state pension funds (NPFs), using predictive analyses of expected returns generated by the Verhulst forecasting equation. The research methodology encompassed system analysis, the Verhulst prognostic equation, dynamic programming models, and conditional optimization based on R. Bellman’s equations. The study’s information and empirical foundation comprised current regulatory legal acts, data from the Federal State Statistics Service (Rosstat), open data from the Central Bank of the Russian Federation (Bank of Russia), analysis of information sources on the activities of domestic NPFs, results of empirical studies by domestic and foreign authors, and information obtained from open sources on the profitability of 22 NPFs of the Russian Federation. The forecast for the period from 2024 to 2063, using the Verhulst forecasting model developed in this study, indicates that the highest value of expected profitability in 2063, specifically 11.66% in annual terms, should be anticipated from the JSC NPF Alliance, while the minimum (3.54% per annum) is expected from the JSC MNPF BOLSHOY. The solution to the dynamic programming problem concerning the optimal distribution of citizens’ pension savings in NPFs demonstrated that the maximum return on investment of pension funds would be achieved under the condition that from 2024 to 2043, funds are invested in JSC NPF FUTURE, and from 2044 to 2063, the funds are invested in the JSC NPF Alliance. The total return on pension savings for the entire investment period (40 years) amounts to 5202%, or more than 52 times the initial investment. Doi: 10.28991/ESJ-2025-09-01-028 Full Text: PDF